Woman exposure to TV advertisements and its role in determining her priorities - Muntadher Khalid Abbood (Genius Journals, 2022)
The development of life in various fields, including industrial development led to an increase in the production of services and goods. This generated a spirit of competition in the promotion of these goods through various forms of advertisements that aim to attract the attention of the consuming public. Among those forms of advertisements are television advertisements that have a major role in promoting services, goods, determining the priorities of women, and influencing their consumer behavior. The research problem is centered around the motives for exposing women to TV ads through answering the basic question about the role of TV ads in determining the priorities of women. The researcher used the descriptive method of the survey study. A hundred questionnaire forms were distributed to girl students of University of Wasit in an irregular and random manner. The results revealed that women’s viewing of television advertisements varied according to the time of watching, the forms of television advertisements, the extent of credibility and modernity in advertisements, and their usefulness. The results also revealed that there is an effective role for TV ads in determining priorities of women
Keywords: Mass media; Tv; Industrial development; Goods; promotion